(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2013)
Based on the data obtained from the previously conducted investigations and field tests, new invetigations have been conducted with the purpose to restore the trouble-free operation of Yerevan Underground and with the aim to drawdown the level of groundwater in the vicinity of some stations. Calculations by hydrogeological methods have shown that capasity of new drainage will be 445.5 L/s that will be discharged by means of gallery. Construction of the new drainage will contribute to steep drawdown of groundwater static level (it will be 3–5 m below the railroad track), particularly in the distance of 50–70 m from the existing drainage that will provide safe and long-lasting operation of the underground.